Internal Faktor Determinan dalam Dinamika Legislasi di Kampung Kayo Batu Kota Jayapura - Karolina R S Wenggi; Akbar Silo; Untung Muhdiarta; Yusuf Gabriel Maniagasi (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2025)
This study aims to analyze the internal determinants that influence legislative dynamics in Kampung Kayo Batu, an indigenous community in the urban area of Jayapura City, Papua. Using a qualitative descriptive approach through case study methods, data were collected through in-depth interviews with formal and informal actors, participatory observation, and analysis of relevant village regulations. Source and method triangulation techniques were used to ensure data validity and credibility. The results show that village legislation faces various institutional challenges, such as low technical capacity for drafting regulations, weak coordination between village heads and Bamuskam, the dominance of local elites, and a lack of legal literacy among officials and the community. In addition, the dualism of authority between the formal government structure and traditional leaders creates legal ambiguity that often hinders policy implementation. A paternalistic and informal institutional culture also weakens substantive participation, especially for women and youth. However, there is an opportunity for reform through the application of a hybrid legislative model based on local wisdom, such as the deliberative “three-stove” framework that integrates the roles of government, customs, and society. Thus, it is important to strengthen institutional capacity, improve legal literacy, and harmonize customary norms and state law in order to create inclusive, legally valid, and sustainable village regulations in the context of urban indigenous communities.